Assembléia de artrópodes associada a duas espécies de plantas mirmecófitas amazônicas e suas formigas especialistas - Lourenço, Waldete Castro (Instituto Nacional de Pesquisas da Amazônia - INPA, 2009)
Myrmecophytes are plants that have hollow structures—domatia—that permit ants to nest inside. These ants protect the plants against herbivores, but the effectiveness of such defense varies among the associated ant species. However, some arthropods have developed associations with myrmecophytes in order to take advantage of the ants’ defensive behavior. Crematogaster laevis (Formicidae: Myrmicinae) is a generalist ant species that can inhabit Maieta guianensis e Tococa bulifera (both Melastomataceae). These two plant species can be found associated with two specific ant partners: Pheidole minutula (Formicidae: Myrmicinae) in M. guianensis and Azteca sp. (Formicidae: Dolichodorinae) in T. bullifera. In this study, we compared the effects of ant presence on anthropod richness and abundance between myrmecophyte and non- myrmecophyte plants. In addition, we investigated whether in myrmecophytes the obligate ant species were more effective in defense than the generalist ant species, and if the ants negatively influenced arthropod richness and abundance in these plants. We showed that both the presence and the identity of the associated ants influenced the structure of the arthropod assemblage. It is likely that this result was a function of the pressure imposed by the ants; the ants that colonize myrmecophytes exclude many arthropod species but allow some arthropod species to colonize the plant. In these specific cases there was a greater abundance of some arthropod species that live exclusively in myrmecophytes, indicating that there is a selective model where arthropods associated with these plants are a function of the associated ant species. Our results demonstrate that differences in the efficacy of ant defense are important in determining and characterizing the arthropods that are able to colonize myrmecophytes. Different plants with different ants host specific arthropod fauna. These arthropods are highly specialized and they are strongly dependent of the presence and the stability of these ant-plant systems.
Keywords: Formigas; Artrópodes; Mutualismo